Effects of inoculum source, pH, redox potential and headspace di-hydrogen on rumen in vitro fermentation yields. (31st March 2014) - Broudiscou, L. P.; Offner, A.; Sauvant, D.
<x content-type="archive" xml:space="preserve">Abstract</x> This in vitro study aimed at understanding how abiotic, that is chemical and electrochemical potentials, and biotic factors combine to impact the outputs of rumen volatile fatty acid (VFA). Using a 48-run design optimized by means of an exchange algorithm, the curvilinear effects of pH, Eh and partial pressure of dihydrogen (H2) on fermentation yields were investigated in 6-h batch cultures of mixed rumen microbes, fed on glucose so as to bypass the enzymatic hydrolysis and conversion steps preceding the glycolytic pathway. The role played by rumen microbiota in the expression of these effects was explored by testing three inocula grown on feeds supplying a microflora adapted to fibre, slowly degradable or readily degradable starch as the dominant dietary polysaccharide. Data were fitted to 2nd-order polynomial models. In fibre-adapted cultures, the yields of major VFA were mainly influenced by pH and H2 partial pressure, in opposite ways. In wheat grain-adapted cultures, the VFA yields underwent the opposite influences of pH, in a curvilinear way for propionate, and Eh since acetate production yield was not significantly modified by any factor. In maize grain-adapted cultures, acetate production yield was not modified by any factor but H2 in a quadratic way when the production yields of higher VFA underwent opposite influences of pH and Eh. In conclusion, the effects of environmental factors were dependent on the nature of the inoculum, a major source of variation, and more particularly on its adaptation to high- or low-fibre diets. These effects were loosely interrelated, the pH being the most active factor before the Eh and H2 partial pressure.